The Role of Palliative Surgery for Malignant Bowel Obstruction and Perforation in Advanced Microsatellite Instability-High Colorectal Carcinoma in the Era of Immunotherapy: Case Report - Judge, Sean J.; Ji, Jingran; Liu, James; Kaur, Manmeet; Kim, Edward; Gong, Jun; Tam, Kit W.; Kirane, Amanda R.; Gholami, Sepideh; Canter, Robert J.; Bold, Richard J.; Gangi, Alexandra; et al. (Frontiers in Oncology, 2020)
The role of palliative surgical interventions in the management of acute complications in patients with disseminated malignancy remains controversial given the complexity of assessing acute surgical risk and long-term oncologic outcome. With the emergence of checkpoint blockade immunotherapy as potentially transformative treatment, there appears to be an increasing role for historically palliative procedures as a bridge to systemic immunotherapy. This is especially evident in advanced microsatellite instability-high (MSI-H) colorectal cancer where malignant obstruction and fistula formation are more common and where immunotherapy with checkpoint blockade inhibitors (anti-PD-1/PD-L1, anti-CTLA-4) have a high response rate with potential for favorable oncologic outcomes. We present a series of three patients with MSI-H metastatic colorectal cancer complicated by malignant bowel obstruction and fistula formation, who having progressed on standard chemotherapy, underwent palliative intervention with the intention of starting immune checkpoint blockade with durable and clinically meaningful anti-cancer responses. These cases highlight the need to re-evaluate the role of historically palliative operations in the setting of disease progression for immunotherapy-responsive tumors.